2015
DOI: 10.1016/j.bjorl.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contralateral stimulation on acoustic reflectance measurements

Abstract: The activation of the auditory efferent pathways through contralateral acoustic stimulation produces alterations in response patterns of acoustic reflectance, increasing sound reflection and modifying middle ear acoustical energy transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…While reflexes elicited by 0.5 kHz and 1 kHz pure tones in stimulus presentation in the presence of contralateral noise had acceptable reliability, they were not found reliable at 2 kHz [39]. On the other hand, Pichelli et al [38] evaluated chirp stimulus at 2 kHz and showed that muscle response tended to increase when efferent suppression was activated compared with the test condition with contralateral noise. The results of these two studies agree with each other and show that low frequencies are more reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While reflexes elicited by 0.5 kHz and 1 kHz pure tones in stimulus presentation in the presence of contralateral noise had acceptable reliability, they were not found reliable at 2 kHz [39]. On the other hand, Pichelli et al [38] evaluated chirp stimulus at 2 kHz and showed that muscle response tended to increase when efferent suppression was activated compared with the test condition with contralateral noise. The results of these two studies agree with each other and show that low frequencies are more reliable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies showed that higher acoustic reflex thresholds were obtained in the presence of contralateral noise stimuli [38][39][40], and when reflex latencies were examined, it was observed that the latencies for on-time reflexes were lengthened while those for off-time reflexes were shortened [41]. The articles reviewed in this study on frequency are summarized in Table 3.…”
Section: Frequencymentioning
confidence: 90%